2013
DOI: 10.1051/0004-6361/201321677
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet to near-infrared spectroscopy of the potentially hazardous, low delta-V asteroid (175706) 1996 FG3

Abstract: Context. Primitive near-Earth asteroids (NEAs) are important subjects of study for current planetary research. Their investigation can provide crucial information on topics such as the formation of the solar system, the emergence of life, and the mitigation of the risk of asteroid impact. Sample return missions from primitive asteroids have been scheduled or are being studied by space agencies, including the MarcoPolo-R mission selected for the assessment study phase of ESA M3 missions. Aims. We want to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A coarse-grained surface for 2001 SN263 could possibly explain the above mismatch and would also support the hypothesis by Delbo et al (2011): these authors suggested a regolithdepletion mechanism during binary asteroid formation and noted that a unique system (i.e., very spaced triple components) such as 2001 SN263 could potentially be dramatically affected by this effect. Noteworthy, surface variations possibly related with binary nature have already been suggested for the NEA (175706) 1996 FG3 (Perna et al 2013a;de León et al 2013).…”
Section: Spectramentioning
confidence: 75%
“…A coarse-grained surface for 2001 SN263 could possibly explain the above mismatch and would also support the hypothesis by Delbo et al (2011): these authors suggested a regolithdepletion mechanism during binary asteroid formation and noted that a unique system (i.e., very spaced triple components) such as 2001 SN263 could potentially be dramatically affected by this effect. Noteworthy, surface variations possibly related with binary nature have already been suggested for the NEA (175706) 1996 FG3 (Perna et al 2013a;de León et al 2013).…”
Section: Spectramentioning
confidence: 75%
“…Consequently, rather than analyzing each taxon separately, in the following we define four major groupings to increase the significance of our analysis (also in terms of impact risk mitigation purposes): the "silicaceous" asteroids (184 PHAs in total), including the whole S-complex together with objects classified as Q-, A-, or O-type; the "basaltic" V-type asteroids (12 PHAs); the "carbonaceous" asteroids (40 PHAs in total), consisting of PHAs belonging to the B, C, D, P, T, and Xc classes (we stress that the only Xc-type in our sample is (175706) 1996 FG3), which clearly is of primitive nature (see Perna et al 2013b and references therein); the remaining "miscellaneous" asteroids (25 PHAs in total), i.e., those classified in the X, Xe, Xk, K, and L taxa. As stated above, such a grouping will include objects of either silicaceous, carbonaceous, enstatitic, or metallic nature (see Fornasier et al 2011 for a review on X-type asteroids).…”
Section: The Pha Population: a Statistical Analysismentioning
confidence: 88%
“…We found 17 C-complex and five D-type objects, all bodies pertaining to taxonomic classes linked with a primitive composition and known to be extremely rare among the low ∆V population (Kuroda et al 2014). Incidentally, two of them have already been chosen as a sample-return candidate: (101955) Bennu, target of the OSIRIS-REx mission (Lauretta et al 2017), and (175706) 1996 FG3, backup target of the ESA candidate mission MarcoPolo-R (Perna et al 2013b). In addition, we also considered three A-type PHAs in this subgroup: a type of olivine-dominated asteroid extremely rare in both the NEO population and the asteroid belt (see also Popescu et al 2018).…”
Section: Selection Of Potential Targets Of Space Missionsmentioning
confidence: 98%